Policies for Making the Chilean Labour Market More Inclusive - Caldera Sánchez, Aida (OECD Publishing, 2014)
Economic growth and recent policy reforms have increased employment and reduced overall poverty in Chile. Yet there are some groups that remain at the margins of the labour market and could benefit from and contribute more to growth. Women and young people have entered the labour force in greater numbers, but their participation rates remain low compared to most OECD and Latin American countries. The participation of women in the labour market is held down by economic, cultural and regulatory barriers. For youth, poor basic skills acquired through compulsory education and the weak linkages between secondary education and job related skills often limit their employment prospects. Among lowskilled workers, a high minimum wage and strict employment protection pose a barrier to employment. At the same time, education and training policies do not sufficiently reach those with poor skills and the public employment services lack the capacity to deliver high quality job-search services. The paper discusses a number of policies that could help to make the Chilean labour market more inclusive and broaden the benefits of growth. These include expanding childcare, promoting a more flexible labour market and strengthening education and skills policies, among others. This Working Paper relates to the 2013 OECD Economic Survey of Chile (www.oecd.org/eco/surveys/economic-survey-chile.htm)
Keywords: Employment; Economics; Chile